Mostruário de Práticas: Considerações sobre a formação e a atuação de professores dos Anos Iniciais a partir das Feiras Catarinenses de Matemática - Da Silva, Viviane Clotilde [UNESP]; Garnica, Antônio Vicente Marafioti [UNESP] (FapUNIFESP (SciELO), 2015)
This research aims to present and analyze narratives that, as a whole, allowed assigning meaning to conceptions and practices related to the teaching and learning of mathematics in the elementary schooling system in the State of Santa Catarina. In this scenario, the Mathematics Fairs of Santa Catarina is noteworthy. Using the methodology known as Oral History, depositions of fifteen active teachers at the beginning of formal schooling were collected, edited and studied , all of them involved with mathematics fairs. Their narratives emphasize aspects of the elementary teachers formation in Brazil, some possible strategies for their in-service preparation and allows us to understand some of the expectations of these elementary teachers in their daily activities related to Mathematics.
A collection of practices: Some remarks on teacher's formation and the Mathematical Fairs of Santa Catarina (Brazil)
Keywords: Mathematics Education; Mathematics Fairs of Santa Catarina-Brazil; Narratives; Practices; Teachers Formation of Initial Years of Formal Schooling